Combination of recombinant factor VIIa and fibrinogen corrects clot formation in primary immune thrombocytopenia at very low platelet counts. (15th November 2012) - Larsen, Ole H.; Stentoft, Jesper; Radia, Deepti; Ingerslev, Jørgen; Sørensen, Benny
Summary Haemostatic treatment modalities alternative to platelet transfusion are desirable to control serious acute bleeds in primary immune thrombocytopenia (ITP). This study challenged the hypothesis that recombinant activated factor VII (rFVIIa) combined with fibrinogen concentrate may correct whole blood (WB) clot formation in ITP. Blood from ITP patients (n = 12) was drawn into tubes containing 3·2% citrate and corn trypsin inhibitor 18·3 μg/ml. WB [mean platelet count 22 × 109/l (range 0–42)] was spiked in vitro with buffer, donor platelets (+40 × 109/l), rFVIIa (1 or 4 μg/ml), fibrinogen (1 or 3 mg/ml), or combinations of rFVIIa and fibrinogen. Coagulation profiles were recorded by tissue factor (0·03 pmol/l) activated thromboelastometry. Coagulation in ITP was characterized by a prolonged clotting time (CT, 1490 s (mean)) and a low maximum velocity (MaxVel, 3·4 mm × 100/s) and maximum clot firmness (MCF, 38·2 mm). Fibrinogen showed no haemostatic effect, whereas rFVIIa reduced the CT and increased the MaxVel. The combination of fibrinogen and rFVIIa revealed a significant synergistic effect, improving all parameters (CT 794 s, MaxVel 7·9 mm × 100/s, MCF 50·7 mm) even at very low platelet counts. These data suggest that rFVIIa combined with fibrinogen corrects the coagulopathy of ITP even at very low platelet counts, and may represent an alternative to platelet transfusion.